Assessment of storage containers effect on stability of cannabis metabolites in urine using Liquid Chromatography-Tandem Mass Spectrophotometry technique - Idris Mohammed; Eiman Awadh Abdullah; Aisha Al-Shehi; Mussab Osama; Gavash Harsha Kannikant (International Journal of Medical Toxicology and Legal Medicine, 2024)
∆9-Tetrahydrocannabinol (∆9 -THC) metabolites such as THC-OH (11-Hydroxy-Δ9-tetrahydrocannabinol), THC-COOH (11-Nor-9-carboxy-Δ⁹-tetrahydrocannabinol) and THC-COOH-glucuronide (11-Nor-9-carboxy-Δ⁹-tetrahydrocannabinol conjugate) were studied in urine samples for their stability with respect to different storage conditions involving containers, temperature and time using validated liquid chromatography – tandem mass spectrometry method. It was concluded that storing the samples for less than three months either at 4 ºC or -20ºC in the silanized clear or amber glass was desirable.